Needs Analysis in Role Playing Learning Model Influence on Motivation and Biology Learning Outcome of the Students at SMA Negeri 3 Samarinda - Djumroh Rosifah; Muh Amir Masruhim; Sukartiningsih Sukartiningsih (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2018)
This study addresses four domains: 1) description of Role Playing learning model use as a learning strategy in Biology instructional process at school, 2) perspectives and threats obtained by teachers at school when addressing Protein Synthesis topic 3) Role Playing learning model in Protein Synthesis topic of Biology learning, 4) the influence of Role Playing learning model towards motivation and Biology learning outcome. The results of this study is teacher needs analysis instruments, analysed using descriptive qualitative. The study showes that the use of Role Playing Instructional Model during Biology learning process has not been performed at school according to three reasons: 1) obstacles obtained when addressing the topic which is difficult to observe, 2) the difficulties obtained when addressing Protein Synthesis topic, in this case, teacher needs to apply Role Playing instructional Model to engage students with their environment, 3) Role Playing as an instructional model that demands students to learn from their experience in order to motivate and improve their learning outcomes.